WOMEN SELF HELP GROUPS- A WAY FORWARD FOR SUSTAINABLE LIVELIHOOD. - Kumari, R. Meena; S. Anandhi,; C Mahajan, Vaishali; K. Rajgopal, (The journal of contemporary issues in business and government, 2022)
SHGs (Self Help Groups) are a widespread mechanism for women development especially in rural areas by solving their problems at the grassroot level. In order to facilitate livelihood opportunities for women, these SHGs play a substantial role. In this study, an attempt has been made to assess the impact of Institutional support, Marketing strategies adopted by the group members to sell the product, and the Empowerment level among the members of women SHGs on Sustainable Livelihood activities. A structured questionnaire was prepared in the local language, data was collectedfrom Sivagangai, Ramanathapuram, and Pudukottai districts in Tamilnadu. The samples chosen for the study were around 150 members from different women SHGs.Data was processed using the SPSS package.One-way ANOVA, Multiple Regression and Pearson Correlation were used to analyze the data obtained. The study concluded that there is a significant relation between Sustainable livelihood and Institutional support, Marketing strategies and Women Empowerment. It was also found out that the number of SHG members and the number of years the SHG group has been formed significantly influences Sustainable Livelihood, Institutional support, Marketing strategies, and Women Empowerment.